GENE EXPRESSION AND SINGLE NUCLEOTIDE POLYMORPHISM (rs1140713) OF MICRORNA-126 - W. L. Abdullah,; R. M. Abed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
MicroRNAs are non-coding gene regulators that may serve as systemic lupus erythematosus biomarkers for diagnosis or prognosis. This study was aimed to identify the single nucleotide polymorphism (rs1140713) of microRNA-126 and its expression by using PCR and qRT-PCR techniques. This research involved 100 womenwith SLE with a mean age of 32.85±9.992 years they were obtained from Baghdad city (medical city, Baghdad Hospital)/Iraq, along with 100 healthy controls with a mean age of 31.68±8.308 years. The mean score on the SLE disease activity index (SLEDAI-2k) was 10.860.±3.275  and a disease duration was 9.00 years, (Erythrocyte sedimentation rate, C-reactive protein, urea, and creatinine were all significantly higher in SLE patients compared to controls, while haemoglobin, white blood cells, complement 3, and complement 4 were significantly lower in contrast to controls (p-value=< 0.0001**)). According to the examination of anti-nuclear antibodies (ANA) in patients, 89% of them have ANA and 95% have anti-double strand DNA (anti-dsDNA) antibodies. Single nucleotide polymorphism analysis for subjects involved in this study revealed a significant increased risk association between miRNA-126 (rs1140713) heterozygote (CT)(OR=20.64; p≤0.001) and homozygote mutant (TT) (OR = 16.35; p= 0.001) genotypes and SLE incidence. Moreover, the results showed a substantial decline in microRNA-126 expression with fold change mean (0.639±2.931) in comparison to controls' fold change mean (1.00±0.00). The present investigation found no indication of a relationship between changes in microRNA-126 folds and demographic or laboratory studies of the disease. The results suggest the microRNA-126 might consider as biomarkers in SLE pathogenesis.